Nutritional Status and Food Consumption Pattern in Disadvantaged Areas of Madhya Pradesh - V. Sangeetha, Premlata Singh, Satyapriya, G. S. Mahra P. Venkatesh, V. Lenin and A. K. Singh (Indian Journal of Extension Education, 2018)
Diet and diversity is very important to lead a quality and healthy life. It plays a major role in deciding the nutrition status of a person. It gets increased attention because of its impact on nutrition and health. Astudy was conducted in this line in Dhar and Datia districts of Madhya Pradesh, a nutritionally disadvantaged area. Astructured interview schedule was the tool for data collection with in-built 24-hour diet recall section. The respondent group comprised of 30 men, 30 women, 30 boys and 30 girls in one district. Atotal of 240 respondents from both districts participated in this study. The study registered a slight mark of overweight and obesity in the respondent groups. It was understood from the study that the problem of under nourishment was less with male groups than female groups in both districts. It was also revealed in this study that majorly, the respondent groups had low level of knowledge about nutrition. Asixteen food group model (FAO) was used to evaluate Diet Diversity (DD) individually based on the number of food groups consumed in the previous 24hours period. DD score (DDS) ranging from 0 to 7 was constructed. The DDS terciles for low, medium and high were also constructed. The actual consumption of all the food groups taken by the respondents were quantified and it was found that mostly food was consumed about 50 per cent less than the recommended dietary allowance across all the categories. The most consumed food groups were cereals, vegetables, milk and milk products and the least consumed were pulses and fruits. Overall IDDS was medium ranging from 3.9 to 4.7 (Dhar) and 5.0 to 6.4 (Datia). Even though, minor difference was noticed in the score between the different groups; there was no significant difference between male and female groups. In conclusion dietary diversity is poor and efforts to improve nutritional status must address the issue of nutrition education, dietary diversity and nutrition sensitive agriculture.